Toward a novel multi-century archive of tree mast using pollen from lake sediments. (November 2022) - Prebble, Joseph G; Dunbar, Gavin; van den Bos, Valerie; Li, Xun; Vandergoes, Marcus; Richardson, Sarah; Horgan, Huw; Holt, Katherine A; Howarth, Jamie; Levy, Richard
Mast seeding – the pronounced inter-annual variability and synchrony in seed production – can have profound local ecological impacts. We explore the potential for generating long (centuries to millennia) proxy records of tree mast seeding, from pollen deposited in lake sediments. This proxy record uses pollen recovered from annually-banded (varved) sediments from a core collected from Lake Ohau, South Island, New Zealand to reconstruct masting events for two genera of Southern Beech, Fuscospora spp. and Lophozonia spp. We find average mast frequencies inferred from Fuscospora pollen from a 43-year sediment core collected from Lake Ohau comparable to seed fall expected for the catchment using a differential-temperature (ΔT) statistical model for the period 1974–2016. In contrast, Lophozonia pollen mast frequency in the 1974–2016 timeseries was consistently lower than that predicted by the ΔT model, although the patterns of variability were broadly similar. We explore this approach in a second 32-year pollen timeseries from Lake Ohau, spanning the pre-instrumental period 1833–1864. During this interval, average air temperature was 1°C cooler than the late 20th century, and interannual variability of air temperature was subdued, such that mast frequency predicted by the Δ T model is the lowest in 200 years. We find mast frequency in our pollen records reflects this pattern for Fuscospora, with a minima of mast frequency from 1850, compared to the 1974–2016 record, but not for Lophozonia . This paper demonstrates that a centuries-long pollen record from the Lake Ohau sedimentary sequence has the potential to form a valuable proxy for Fuscospora masting that would supplement existing seedfall records. Long records of this type could significantly enhance our understanding of the environmental drivers of mast seeding.